Attitudes of Parents Toward Child-Rearing: A Case Study - I. Celik; M. Halmatov; H. Saricam (University of Sofia, 2012)
The aim of this study is the investigation of parents', living in rural areas or urban areas and with children 5-6 years of age, difference in their attitudes towards children according to demographic characteristics and living conditions, rural and urban areas. The study group of the research includes 200 parents who have 5-6 years old children taking pre-school education. 100 of them live in rural areas and 100 of them live in the city center. Instruments of study are Personal Information Form and PARI (Family Life and Child-Rearing Attitude Scale). Independent samples t-test, ANOVA and Regression Analysis were used for data analysis. According to findings, mothers are more over-protective, more democratic and less disciplined than fathers. Parents living urban areas are more over-protective, more democratic and less disciplined than parents living rural areas. Moreover, parents living in extended families are more disciplined, less over-protective and less democratic egalitarian in terms of attitudes than parents live in nucleus families. As a result, educational status, gender, family type and location are predictors for parents' child-rearing attitude. However, the variables of age and number of children do not contribute to the total variance significantly.